Impact of Economic Freedom and Educational Attainment on Life Expectancy: Evidence From the New EU Member States - Moga Rogoz, Adrian Teodor; Sart, Gamze; Bayar, Yilmaz; Gavriletea, Marius Dan (Frontiers in Public Health, 2022)
Life expectancy is a significant indicator of public health, life quality, welfare and economic development. Therefore, improvement in life expectancy is among the priority targets that need to be achieved across the EU countries. This paper investigates the effect of economic freedom and educational attainment on life expectancy in the new EU member states, experiencing an institutional, educational, and economic transformation, during the period 2000-2019 by using cointegration and causality tests, because economic freedom and educational attainment can foster the life expectancy through institutional and economic variables such as institutions, governance, sound monetary and fiscal policies, economic growth, innovation, technological development, better living standards and access to superior healthcare services. The causality and cointegration analyses revealed that economic freedom and educational attainment were significant determinants of life expectancy in the short and long term. However, educational attainment was found to be more effective on life expectancy than economic freedom. The findings have important implications for educational and health policies in analyzed countries. Governments must understand the education–health relationship to be able to develop and promote educational policies that have the potential to improve public health.